Representative roughness height of submerged vegetation - Cheng, Nian-Sheng (2011)
Roughness length scale is important in the evaluation of resistance caused by submerged vegetation in open channel flows. By transforming the concept of hydraulic radius, a representative roughness height is proposed in this study for quantifying effect of submerged vegetation on flow resistance in the surface layer. The proposed roughness height is characterized by its proportionality to both stem diameter and vegetation concentration and performs better than other length scales in collapsing resistance data collected under a wide range of vegetation conditions. An approach is then developed for estimate of the average flow velocity and thus resistance coefficients for both cases of rigid and flexible vegetation. Comparisons are also made between the present study and other four formulas available in the literature. This study also shows that all the formulas, if simplified for some simple conditions, can be unified in a general form.